Transport and Charge Carrier Chemistry in Lithium Sulfide. (20th December 2018) - Lorger, Simon; Usiskin, Robert E.; Maier, Joachim
Abstract: Lithium sulfide is a functional material of great importance for battery research, since it is the discharge product in Li–S cathodes and a frequent component of anode passivation layers. In both cases, transport of charge carriers in Li2 S is critical for performance. The exploration of charge carrier chemistry in such a simple binary compound is also of fundamental scientific interest. For that purpose, impedance spectroscopy and electromotive force measurements are performed over a broad range of temperatures and doping conditions. The results indicate predominant ion conduction and can be quantitatively explained by a defect chemical model based on Frenkel disorder and vacancy‐dopant association. Mobilities and migration barriers for both vacancy and interstitial defects are deduced. The thermodynamic and kinetic parameters derived for Li + transport in antifluorite Li2 S show remarkable agreement with the analogous parameters for F − transport in fluorite compounds such as BaF2, thereby improving the structural understanding of charge carrier chemistry in such compounds. An application of these results to passivation layers in solid state batteries is also discussed. Abstract : Charge carrier chemistry and transport are critical to the function of Li2 S as a discharge product and a passivation layer in batteries. Transport measurements and defect chemical analysis reveal predominant ion conduction that is well described by a model based on Frenkel disorder and migration of both Li + vacancies and interstitials.